8Rs for circular water and sanitation systems: leveraging circular economy thinking for safe, resilient and inclusive services - Carrard, N.; Kumar, A.; Dao, D. V.; Kohlitz, J.; Retamal, M.; Taron, Avinandan; Neemia, N.; Willetts, J. (Elsevier, 2024)
To achieve their normative health, environmental and social objectives, water and sanitation services must be safely managed, inclusive and climate resilient. Meeting these imperatives presents a need and opportunity for innovative thinking about water and sanitation service systems. Circular economy concepts are being applied across a multitude of product and service sectors with the aim to facilitate regenerative flows of resources. Given the dependence on water resources, associated climate risks, and the generation of reusable waste products in water and sanitation service delivery, circular economy concepts can be usefully leveraged to drive sustainability outcomes. This article contributes a heuristic in the form of a conceptual framework for applying circular economy concepts in the design and delivery of water and sanitation services in diverse Global South contexts. The framework seeks to drive multiple outcomes relevant to water and sanitation initiatives: safely managed services, social inclusion, and climate resilience. Co-developed by an international research team applying a theoretical multiplicity approach and collaborative sensemaking, the heuristic takes the form of a suite of eight adapted circular economy ‘R strategies’ for water and sanitation. The R strategies were selected and articulated to reflect theory-based principles of circular economy, climate resilience and inclusion. They are intended to prompt thinking and action in pursuit of safely managed, climate resilient, inclusive water and sanitation services that align with the broader sustainability directions that circular economy narratives aspire to. The heuristic offers a conceptually rigorous, practical tool that can support collaborative, deliberative processes to realise the potential benefits of circularity in water and sanitation service systems.